The Making of Android-Based Administration Service Application (A Case Study on Village Administrative Office in Jenggala) - Suckma Azani; Muhammad Benny Chaniago (Association for Scientific Computing Electrical and Engineering, 2020)
The village administrative office in Jenggala village is one of the office that has troubles or problems in doing services to the public especially in making official letters. The lack of facilities in managing and making official letters applied by the public can disrupt the performance of the staff and slowing down the pace in providing the official letters. There are some problems that is happening in the office such as the general administrative job is still done manually, the working hour in the office is limited, the lose of the public data that has already submitted in advance, and the making of report is not well-organized so that the head officer do not know both all the reports and the reports submitted in certain period of time. The researcher aims to create the android-based administration service application to facilitate the public in making the official letters as needed. The application is designed as a tool of fast, precise, and effective communication between the public and the officer. The application was built to facilitate the village government in managing the reports in making official letters delivered by the citizen of Jenggala. Therefore, the application is expected to provide convenience and flexibility in making official letters in Jenggala Village.